Disruption in the Arts Textual, Visual, and Performative Strategies for Analyzing Societal Self-Descriptions - Koch, Lars; Nanz, Tobias; Pause, Johannes (Culture & Conflict, 2018)
The volume examines aesthetic disruptions within the various arts in contemporary culture. It assumes that the political potential of art is not solely derived from presenting its audiences with openly political content. Rather, it creates a space of perception and interaction using formal means, thus problematizing the self-evidence of hegemonic structures of communication.